Temperature dependence of absorption band edge of CdTe nanocrystals in glass - Allahverdi, C.; Yukselici, M. H. (IOP PUBLISHING LTD, 2008)
CdTe nanocrystals were grown in borosilicate glass by two-step heat treatment process. Their average radii between 2.98 +/- 0.07 and 6.15 +/- 0.32 nm are determined by using effective mass approximation in the strong confinement limit. The changes in the band gap of CdTe nanocrystals with temperature in the range from 300 to 775 K are found to be between -5.43 x 10(-4) and - 3.78 x 10(-4) eV K-1 by using Varshni's empirical temperature-dependent band gap energy change relation. The difference between temperature dependence of band gap energy for CdTe nanocrystals and that of bulk CdTe crystal is proposed to be due to electron-phonon coupling which is stronger in nanocrystals. We also report a method to estimate glass transition temperature on the basis of analysis of temperature dependence of absorption band edge of CdTe nanocrystals in glass.
Keywords: OPTICAL-ENERGY GAP; Physics